OP0238 Patients with Ankylosing Spondylitis Have an Increased Proportion of CD16+ Dendritic Cells, Able to Induce CCR6-Expression on CD4+ T Cells. (23rd January 2014) - Wright, P. B.; Utriainen, L.; Firmin, D.; Aumeunier, A.; McEntegart, A.; McCarey, D.; McInnes, I. B.; Milling, S.
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic systemic inflammatory disease primarily affecting the axial skeleton. The genetic association between AS and HLA-B27 was discovered 40 years ago, however the pathogenic role of this molecule remain elusive. IL-17-producing Th17 cells appear to be important in driving pathology both in AS patients 1, and in the HLA-B27 transgenic (B27-TG) rats that provide a model of spondyloarthropathy 2 . Dendritic cells (DCs) activate naïve T cells and maintain the balance between activation and suppression of the immune response. If affected by HLA-B27, DCs are therefore likely to contribute to the T cell-mediated aspects of AS pathogenesis. Studies in our laboratory using B27-TG rats, have uncovered deficiencies in tolerogenic DC populations 3 that may contribute to disease development. Objectives: Following our studies in the B27-TG rats we hypothesised that AS patient DCs would also be altered, contributing to the alterations in T cells previously observed in AS patients. We aimed to characterise and compare the functions of DC populations between AS patients and healthy controls, to understand the role of DCs in AS pathogenesis. Methods: T cell and DC subsets isolated from B27-TG rats, HLA-B7-transgenic controls (B7-TG), from AS patients and age-matched healthy controls were analysed using multiparameter flow cytometry. DC subsets, purified by flow cytometric sorting, were co-cultured with allogeneic T cells; T cell proliferation was measured by CFSE dilution and chemokine expression by flow cytometry. The concentration of IL-23 in plasma samples was measured by ELISA. Expression of CCR6 in rat T cells was analysed by quantitative PCR. Results: We observed that the expression of CCR6 on CD4 + activated T cells is higher in B27-TG rats than in the B7-TG control animals. Blood from AS patients also contains increased proportions of CD4 + CCR6 + activated T cells. When subsets of human DCs were examined, blood from AS patients contained a significantly higher ratio of pro-inflammatory (CD16 + CD14 - CD11c + ) DCs, and higher concentrations of IL-23. In co-culture experiments, these CD16 + DCs induce CCR6 expression on responding naïve T cells. Conclusions: CCR6 expression in T cells is associated with a Th17 phenotype. Our data indicate that, along with the increase in systemic levels of IL-23 in AS patients, a shift of their DCs towards the CCR6-inducing CD16 + population may contribute to the induction of T cell-mediated pathogenesis. References: Bowness P, Ridley A, Shaw J, et al. Th17 cells expressing KIR3DL2+ and responsive to HLA-B27 homodimers are increased in ankylosing spondylitis. J Immunol . 2011;186(4):2672–2680. Glatigny S, Fert I, Blaton MA, et al. Proinflammatory T helper 17 cells are expanded and induced by dendritic cells in spondyloarthritis-prone HLA-B27 transgenic rat. Arthritis Rheum . 2011. Utriainen L, Firmin D, Wright P, et al. Expression of HLA-B27 causes loss of migratory dendritic cells in a rat model of spondylarthritis. Arthritis Rheum . 2012;64(10):3199–3209. Acknowledgements: Funding for this project was provided by Arthritis Research UK (LU, DF, AA), and by the Nuffield Foundation's Oliver Bird Programme (PW). Disclosure of Interest: None Declared